COMPARATIVE PATHOGENICITY OF THE ROOTKNOT NEMATODE MELOIDOGYNE INCOGNITA TO FOUR COWPEA VARIETIES - BABATOLA, J. O.; ADALEMO, K. D. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The role of the rootknot nematode Meloidogyne incognita on nodulation, growth, and grain yield of four cowpea varieties were investigated in pot experiments. All the four varieties did not form nodules when inoculated with 4,000 eggs and juveniles per pot. However, Vita 5 and Il 124-5M form nodules better than Ife-Bimpe and TVX-3236 at lower inoculum levels. Dry shoot weight, root length and plant height varied significantly among varieties and between the levels of rootknot nematode inoculations. Flowering was delayed for up to 46 days in cvs Vita-5, Ife-Bimpe and TVX3236 depending on the levels of inoculum. Flowering was not significantly delayed in cv IT 124-5M at all inoculum levels. Crain yields were reduced by 41.20%, 85.80% and 96.60% in cvs Vita 5, TVX 3236, Ife-Bimpe respectively. Despite high root gall indices in cv IT 124-5M, it out-yielded all varieties at all inoculum levels in this study.